2017
DOI: 10.1017/s0954579417001341
|View full text |Cite
|
Sign up to set email alerts
|

Using an adoption–biological family design to examine associations between maternal trauma, maternal depressive symptoms, and child internalizing and externalizing behaviors

Abstract: Maternal trauma is a complex risk factor that has been linked to adverse child outcomes, yet the mechanisms underlying this association are not well understood. This study, which included adoptive and biological families, examined the heritable and environmental mechanisms by which maternal trauma and associated depressive symptoms are linked to child internalizing and externalizing behaviors. Path analyses were used to analyze data from 541 adoptive mother–adopted child (AM–AC) dyads and 126 biological mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 95 publications
(107 reference statements)
1
12
0
Order By: Relevance
“…The earlier study, with a smaller sample size, found no evidence for genetic nurture 43 , whereas the subsequent study with three times the sample size identified a genetic nurturing effect on offspring depressive symptoms that was mediated by maternal emotional symptoms 44 . This finding is in line with the studies reviewed above which showed environmental associations between maternal depression and offspring internalising behaviours 20 , 21 , 24 and shows that seemingly environmental associations between parental factors and offspring outcomes may nonetheless be driven by genetically influenced parental traits.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The earlier study, with a smaller sample size, found no evidence for genetic nurture 43 , whereas the subsequent study with three times the sample size identified a genetic nurturing effect on offspring depressive symptoms that was mediated by maternal emotional symptoms 44 . This finding is in line with the studies reviewed above which showed environmental associations between maternal depression and offspring internalising behaviours 20 , 21 , 24 and shows that seemingly environmental associations between parental factors and offspring outcomes may nonetheless be driven by genetically influenced parental traits.…”
Section: Resultssupporting
confidence: 91%
“…This is in line with twin literature which shows that depression is a heritable phenotype 3 . After accounting for genetic effects, parental depression was associated with offspring internalising behaviours through environmental pathways, and these associations were observed throughout childhood 20 , 21 , 24 , 25 , adolescence 19 , 26 , and adulthood 23 . Similarly, associations between parental anxiety and offspring internalising behaviours also showed evidence of environmental transmission across development, from toddlerhood to early adulthood 27 – 32 .…”
Section: Resultsmentioning
confidence: 98%
“…enced by the (nonbiological) adoptive parents' behaviors, which themselves are thought to be in part genetically influenced (Rhoades et al 2011;Grabow et al 2017). Molecular studies have identified the influence of nontransmitted parental alleles on offspring's educational attainment.…”
Section: The Meaning Of Cause In Geneticsmentioning
confidence: 99%
“…For maternal depressive symptoms, one meta‐analysis found small, yet consistent, effects of maternal depressive symptoms on child internalizing behavior and on general child psychopathology (Goodman et al, 2011). Most often, associations between maternal depressive symptoms and child internalizing behavior emerge when maternal depressive symptoms are assessed as a chronic exposure (i.e., aggregated over an extended period; Grabow et al, 2017; Pemberton et al, 2010) versus a time‐specific exposure (Hails et al, 2018). This pattern is consistent with extant findings in which persistent maternal depressive symptoms are associated with increased risk for child internalizing behavior in early childhood and depression in adolescence (Netsi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%